Relation of Tea Ingestion to Salivary Redox and Flow Rate in Healthy Subjects - Pik Han Chong; Qiaojuan He; Suyun Zhang; Jianwu Zhou; Pingfan Rao; Min Zhang; Lijing Ke (Food Science and Human Wellness)
The biochemistry of human saliva can be altered by food intake. The benefits of tea drinking were extensively studied but the influence of tea ingestion on human saliva has not been revealed. The work aimed to investigate the immediate and delayed effect of vine tea, oolong tea and black tea intake on certain salivary biochemistry and flow rate. The saliva samples of healthy subjects were collected before, after and 30 min after tea ingestion. The chemical compositions and antioxidant capacity of tea samples were analyzed to correlate with salivary parameters. Principal component analysis indicated that the effects of vine tea consumption were dominated by increasing salivary flow rate (SFR), production rate of total protein (TPC), thiol (SH), malondialdehyde, catalase activity and antioxidant capacity (FRAP) in saliva. The antioxidant profile of studied tea samples (FRAP, polyphenols, flavonoids) was positively correlated with salivary SFR, TPC, SH and FRAP but negatively correlated with salivary uric acid concentration in saliva.